The Efficiency Links on a Graph in Transportation Network - Kavran, Zvonko; Pašagić, Husein; Toš, Zdravko (Promet - Traffic&Transportation, 2012)
The access to a single vertex of the non-directional transportationnetwork graph can be defined in various ways, but ifwe want to classifY the vertices and at the same time avoid ambiguity,then each of them has to be assigned a certain number.The paper uses the method for detemzining the access to a singlevertex based on the description of the transportation networkusing the symmetrical matrix of incidence. By knowingthe matrix of incidence it is possible to detemzine the eigenvaluesi.e. eigenvectors, and their comparison detemzines the valuesfor single vertices. Apart from describing the method, theconcrete example of the tram network of the city of Zagreb hasbeen analysed. Based on the obtained analysis results, it is possibleto detemzine the efficiency of connecting single vertices inthe considered transportation network, i.e. to propose its improvements.